Potential Effect of Immunotherapy Agents on Cognitive Function in Cancer Patients. (26th August 2019) - Joly, Florence; Castel, Hélène; Tron, Laure; Lange, Marie; Vardy, Janette
Abstract: A paradigm shift is occurring in cancer therapy, where instead of targeting tumor cells, immunotherapy agents (IA) target the immune system to overcome cancer tolerance and to stimulate an antitumor immune response. IA using immune checkpoint inhibitors (CPI) or chimeric antigen receptor T-cells have emerged as the most encouraging approaches to treat cancer patients. CPI are reported to induce moderate-to-severe neurologic immune-related adverse events in less than 1% of patients, whereas chimeric antigen receptor T-cell therapy is associated with frequent neurological toxicities that can be severe or even fatal. Cognitive difficulties have been described following chemotherapy and targeted therapy, but not specifically explored in patients receiving IA. The aim of this review is to establish a picture of the first published studies suggesting some biological and physiopathological effects of IA on cognitive functions among cancer patients. The first results originate from a preclinical study evaluating the role of CPI associated with peripheral radiation on cognitive dysfunction and the recent discovery of the central nervous lymphatic system allowing leukocytes to penetrate the central nervous system. Evaluating possible side effects of IA on cognitive function will be an important challenge for future clinical trials and for better understanding the underlying mechanisms through preclinical animal models.